Studies on Antibody-VSG Interactions on the Surface of Trypanosoma brucei - Leahy, Conor (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2026)
African trypanosomes (Trypanosoma brucei) are among the most widely studied protozoan parasites, due to their remarkable ability to thrive in areas strictly patrolled by host immune components, such as the vasculature and central nervous system. Previously, antigenic variation of the VSG was thought to be the sole mechanism underpinning this persistent survival. However, recently it was found that chronic infection by African trypanosomes also relies on the efficient clearance of surface-bound antibodies. The aim of this thesis was to characterise the clearance of surface-bound immunoglobulin-VSG complexes by trypanosomes at a mechanistic level and to understand the role of the kinesin TbKIFC1 in this process. This clearance was followed by direct (flow cytometry) or indirect (aggregation/disaggregation) methods and a number of important results were obtained. Firstly, the inhibitory effect of knockdown of TbKIFC1 on antibody clearance was confirmed and extended to another VSG variant. A key finding came from single molecule tracking of VSG, which demonstrated that diffusion of VSG is ~27% slower on the surface of TbKIFC1-deficient cells. The involvement of TbKIFC1 in this process requires interaction with membranes, and deletion of this interaction through mutation of the membrane-interacting domain had a deleterious effect on antibody clearance. A small molecule inhibitor of TbKIFC1, AZ82, recapitulated the effect observed on the TbKIFC1 knockdown cells. Secondly, antibody clearance assays demonstrated that clearance involved directed trafficking to the flagellar pocket, revealed by disruption of flagellar attachment/motility, endocytic uptake, revealed by actin-depletion, and proteolytic degradation, revealed by use of an irreversible protease inhibitor. The metabolic requirements for clearance were also investigated. Inhibition of trypanosome alternative oxidase impaired antibody clearance, as did reliance on glycerol metabolism, which may suggest that environmental factors like oxygen availability and carbon source can influence clearance efficiency in vivo. The fate of VSG following clearance was also assessed. Evidence suggests that VSG is not degraded, supporting the view that it is recycled to the surface. Thirdly, an attempt was made to apply controlled biotinylation of VSG as a proxy for the previously expressed VSG following a VSG switch. While a simple and reliable method for controlling and quantifying the level of biotinylated VSG was developed, difficulties with antibody access to the biotin moiety precluded the use of this model as a system for investigating the role of VSG clearance in switchers. This discovery raised the question of antibody access to VSG epitopes in live cells. Finally, this access question was investigated by determining what proportion of VSG-specific antibodies were capable of binding live cells. The proportion of antibody was found to be just ~20% of the total, indicating that the majority of VSG-specific antibody produced by the host is not effective. Although unlikely to be physiologically relevant, the aggregation and disaggregation of T. brucei following antibody binding is a striking phenomenon. The disaggregation of cells was found to occur independently of an external effect i.e. proteolytic degradation of the antibody. Therefore, disaggregation likely represents a shift in the dynamic equilibrium between antibody binding on a single cell and antibody which cross-links cells together. In summation, these results position TbKIFC1 as a key mediator of efficient clearance through its membrane interacting domain which ensures rapid diffusion of VSG on the surface. Flagellar attachment/motility-powered hydrodynamic-sorting drives efficient removal of surface-bound antibodies. Actin-dependent endocytosis facilitates Ig-VSG uptake and lysosomal degradation eliminates bound antibody, while VSG is recycled to maintain the protective coat. Additionally, the dense packing of the VSG coat shields non-surface exposed epitopes from the host humoral response. Immune evasion of T. brucei is therefore multilayered, meaning antigenic variation, efficient antibody clearance, and an extremely dense proteinaceous coat work in tandem to enable persistent infection of the mammalian host.
APPROVED
Keywords: Trypanosoma brucei; Antibody; VSG